Pregnancy Behavior Of Pakistani Women Over Their Reproductive Life Span - Sarah Saleem; Elizabeth M McClure; Rasool Bux; Ameer Shaheed; Robert L Goldenberg; Gregory Pappas (Al Ameen Medical College, 2010)
Objective: To understand pregnancy behavior of Pakistani women over their reproductive life span so as to generate baseline data on prevalence of pregnancy loss and to generate hypotheses for future research. Examination of events over the reproductive life span of a woman rather during a single pregnancy or child birth may be more useful in understanding the birth outcomes. Methods: Data of National Health Survey of Pakistan 1992-94 was used for this analysis as this is the only data available with information on diseases and exposures. Stata Version 9 for complex survey analysis was used with survey weights that reflected the over-sampling of urban areas and the three smaller provinces. Results: 2,947 reproductive age women reported 16,833 pregnancies. More urban (12.6%) than rural (9.2%) and high-middle income (11%) than low-income (9.2%) women reported abortions. Stillbirth rate was almost similar among rural (54/1000) and urban (53/1000) women. After adjusting, hypertension (AOR 1.33; 95% CI 1.02, 1.75) and BMI≥23 kg/m2 (AOR 1.46; 95% CI 1.18, 1.80) remained significantly associated with stillbirth, while middle income (AOR 1.28; 95% CI 1.01, 1.63) and women with BMI≥23 kg/m2 (AOR 1.50, 95% CI 1.19, 1.90) had significantly higher abortion rates. Conclusions: We found a high lifetime adverse pregnancy outcome rates, four-fold that of many developed countries.